Effect of incorporation of raw vermiculite as partial sand replacement on the properties of self-compacting mortars at elevated temperature - Karatas, Mehmet; Benli, Ahmet; Toprak, Hasan Anil (Elsevier Sci Ltd, 2019)
This experimental study was aimed to investigate the effect of elevated temperature on the mechanical properties of self-compacting mortars (SCMs) incorporating raw vermiculite (RVM) as partial sand replacement at the substitution rates of 10%, 20%, 30% and 40%. Within this scope, five SCMs series were prepared, including the control mix consisting of 10%, 20%, 30% and 40% of RVM as fine aggregate on 0-2 mm particle sizes of sand weight basis. A total of 45 specimens of 40 x 40 x 160 mm were fabricated and exposed to water curing for 3, 28 and 90 days for mechanical strength properties. 30 cube specimens of 50 x 50 x 50 mm were fabricated and exposed to curing in water for 28 and 90 days to perform durability tests including water absorption, sorptivity, porosity and density tests. The slump flow diameter, V-funnel flow and viscosity tests were performed to evaluate the fresh characteristics of SCMs. The SCMs specimens were subjected to the temperatures of 300 degrees C, 600 degrees C and 900 degrees C after 28 days curing then cooled to room temperature before performing experiments. The results indicated that the compressive and flexural strengths of all SCMs mixtures has decreased at water curing for all ages as RVM rates increases. The compressive and flexural strengths loss for SCMs incorporating RVM remained very low compared to the strength loss of control samples at all temperature ranges. Mini-slump flow values are acceptable for consistency and workability for many applications. SCMs containing RVM can be used in the production of lightweight concrete with excellent properties such as low density and heat insulation. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Self-compacting mortars; Raw vermiculite; Mechanical properties; Durability properties; Elevated temperature